Translation and cultural adaptation of a prostate cancer screening decision aid - Baptista, Sofia (2020)
H4A Primary Healthcare Research Network scholars programme for support of research. This article was supported by National Funds through FCT - Fundação para a Ciência e a Tecnologia,I.P., within CINTESIS, R&D Unit (reference UIDB/4255/2020)